A 'Sandwich' Specimen Preparation and Testing Procedure for the Evaluation of Non-Structural Injection Grouts for the Re-Adhesion of Historic Plasters. Issue 3 (4th March 2021) - Pasian, Chiara; Piqué, Francesca; Jornet, Albert; Cather, Sharon
ABSTRACT: Non-structural injection grouting aims to stabilise delaminated plaster by introducing in the void, typically between delaminated plaster layers, a compatible adhesive material with bulking properties (the injection grout). Injection grout formulations are firstly tested in the laboratory to determine their performance characteristics including their physical-mechanical compatibility with the original materials (plaster or other building materials). However, laboratory tests on grouts are often not sufficiently representative of actual cases in which the grout sets between two plaster layers. This problem is particularly significant when water vapour permeability, capillary water absorption and adhesion need to be assessed. A study was conducted on the development of a 'sandwich' system (plaster-grout-plaster) to better simulate the real situation. This paper describes a new methodology for such specimen preparation and the adapted procedures for laboratory testing. The results are discussed comparing them with those obtained from standard specimen preparation and testing procedure.